2016
DOI: 10.2147/phmt.s115842
|View full text |Cite
|
Sign up to set email alerts
|

Parental practice of child car safety in Enugu, Southeast Nigeria

Abstract: Child safety restraints and seat belts are regarded as the most successful safety and cost-effective protective devices available to vehicle occupants, which have saved millions of lives. This cross-sectional descriptive study evaluated the practice and use of child car restraints (CCRs) among 458 purposively selected respondents resident in two local government areas in Enugu State, Nigeria. Self-administered questionnaires were sent to parents of children attending private schools who owned a car. Chi-square… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…(20,21,(23)(24)(25) In upper-middle-and lowermiddle-income countries, (31) common themes also included the cost of obtaining a CCR as a barrier, in addition to lack of knowledge and difficult child behaviour. (16)(17)(18)(19)22,26,27) Cultural practices in different parts of the world may explain some of the patterns and responses that were seen. In China and Korea, as in Singapore, some parents and grandparents prefer to hold their babies in their arms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(20,21,(23)(24)(25) In upper-middle-and lowermiddle-income countries, (31) common themes also included the cost of obtaining a CCR as a barrier, in addition to lack of knowledge and difficult child behaviour. (16)(17)(18)(19)22,26,27) Cultural practices in different parts of the world may explain some of the patterns and responses that were seen. In China and Korea, as in Singapore, some parents and grandparents prefer to hold their babies in their arms.…”
Section: Discussionmentioning
confidence: 99%
“…(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) These studies found that parental non-compliance to the use of CCRs is multifactorial. Several potential reasons were identified, ranging from knowledge deficits on the importance of CCRs in the event of a collision (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) to practical barriers, such as facing difficult behaviour when the child refuses to stay in the car restraint (18,21,(23)(24)(25)27) and the prohibitive cost of the car restraint. (19)(20)22,27) The question arises of whether the same factors influence parents' decisions on whether to use child car restraints in Singapore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these studies reported poor knowledge of road signs among commercial drivers; they did not compare knowledge of road signs between intra-city and inter-city commercial drivers. 2,6 Drivers who were married were significantly more likely to have good knowledge of road signs compared to those that are single (unmarried, divorced or separated). The reason is not clear but may be connected with the added responsibility that comes with marriage knowing that they have dependents which they should endeavor to live and take care of.…”
Section: Discussionmentioning
confidence: 99%
“…5 In Nigeria, children account for 21% of all road traffic injury-related deaths and road traffic deaths ranked ahead of the most important causes of infant deaths such as neonatal sepsis, preterm birth complications, proteinenergy malnutrition, neonatal encephalopathy, and meningitis. 5,6 It has also killed more than three times as many adults as maternal disorders and almost twice as many people as tuberculosis. 5 According to the Federal Road Safety Command (FRSC) Enugu State Sector command, in 2017, 758 road traffic accidents (RTAs) occurred in Enugu State, with 115 fatalities.…”
Section: Introductionmentioning
confidence: 99%